Head and Neck Critical Illness Basic and Clinical Research Implications - Tomita, Hiroyuki (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
There are various malignant tumors in the head and neck area, including oral cavity, pharynx, sinonasal cavity, and salivary glands. Squamous cell carcinoma is the most common cancer among head and neck cancers. In salivary glands, there are many types of malignancies that can develop, such as malignant lymphoma, adenoid cystic carcinoma, adenocarcinoma, and mesenchymal tumors. In a clinical setting, imaging, such as computed tomography (CT) and magnetic resonance imaging (MRI), is very important in terms of the prediction of the histological type and the evaluation of the extent of invasion of adjacent structures. In basic research, there are few animal models in head and neck malignancies. In this Special Issue, we broadly discuss the basic and clinical research in head and neck malignancies.